2013
DOI: 10.5935/1518-0557.20130072
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-releasing vaginal ring for luteal phase support after superovulation and intrauterine insemination cycles, a pilot study

Abstract: Objective: The main objective of this pilot study was to determine whether a progesterone-releasing vaginal ring is a good alternative for luteal phase support for patients undergoing intrauterine insemination after ovulation induction with sc gonadotrophins. material and methods: We performed a multi-center study involving three different reproductive medicine units. Patients included were diagnosed with unexplained infertility rFSH (Puregon ®) and ovulation induction with urinary HCG (Pregnyl ®). The day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…We assessed whether our results would change by including only studies with a moderate to low risk of bias. Excluding studies deemed to be at high risk of bias (19,24,43) from our syntheses yielded comparable effect estimates that were the same, or larger than those obtained from the analysis of all included studies. In order to test whether the results of our meta-analysis did not depend on our model choice, we performed a sensitivity analysis using DerSimonian-Laird estimators without Hartung-Knapp adjustments in random effects models for the syntheses of the main outcomes.…”
Section: Sensitivity Analysesmentioning
confidence: 87%
See 3 more Smart Citations
“…We assessed whether our results would change by including only studies with a moderate to low risk of bias. Excluding studies deemed to be at high risk of bias (19,24,43) from our syntheses yielded comparable effect estimates that were the same, or larger than those obtained from the analysis of all included studies. In order to test whether the results of our meta-analysis did not depend on our model choice, we performed a sensitivity analysis using DerSimonian-Laird estimators without Hartung-Knapp adjustments in random effects models for the syntheses of the main outcomes.…”
Section: Sensitivity Analysesmentioning
confidence: 87%
“…We identified fifteen published RCTs comparing progesterone luteal phase support after OS-IUI to placebo or no intervention which reported the outcomes of interest (9,19,24,25,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). With respect to the previous review by Green et al, we identified three additional studies (36,43,45) that met the inclusion criteria specified by the authors but were not included in their review, and one newer study (39).For the present review, we had specified unexplained or mild male infertility as the population of interest; this led to the exclusion of the study by Yacizi et al (45), which included only women with PCOS. Our requirement that ITT, per participant data could be extracted resulted in exclusion of an additional two studies (36,42).…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pero en 153 pacientes receptoras de ovodonación, halló mejor TI (19,9% versus 11,6%, p = 0,006) y TEC (39,8% versus 28,6%, respectivamente) (17) . Otra experiencia del uso de AV en el SFL fue la realizada por Schwarze, en 2013, en parejas de inseminación intrauterina, encontrando mejores TEC en el grupo que utilizó AV, aunque sin diferencias estadísticamente significativas (19,1% en el grupo de AV y 11,3% en el grupo sin SFL) (19) .…”
Section: Discussionunclassified